2016
DOI: 10.1177/1591019916647194
|View full text |Cite
|
Sign up to set email alerts
|

Psychological comorbidities and compliance to interventional treatment of patients with cutaneous vascular malformations

Abstract: Purpose The aim of this study was to assess qualitatively the psychological stressors affecting patients with cutaneous vascular malformations and hemangiomas (CVM-H) and their impact on compliance to interventional treatment. Methods A retrospective chart review was conducted of all patients with CVM-H treated by interventional neuroradiology at a single academic institution during a five-year period (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
1
1
Order By: Relevance
“…The current results are inconsistent with findings from some previous studies, which found either no significant differences with norm data (Berger & Dalton, 2009; Brand et al, 2009; Masnari et al, 2013; Stock & Feragen, 2016; Moyakine et al, 2017) or significantly more emotional and behavioral problems in children with a visible difference (Pope & Snyder, 2005; Kenny et al, 2016). The only previous study on Dutch children with an oral cleft found no differences in emotional and behavioral problems when compared to normative data (Hoek et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…The current results are inconsistent with findings from some previous studies, which found either no significant differences with norm data (Berger & Dalton, 2009; Brand et al, 2009; Masnari et al, 2013; Stock & Feragen, 2016; Moyakine et al, 2017) or significantly more emotional and behavioral problems in children with a visible difference (Pope & Snyder, 2005; Kenny et al, 2016). The only previous study on Dutch children with an oral cleft found no differences in emotional and behavioral problems when compared to normative data (Hoek et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…As patients with comorbid depressive symptoms typically suffer from decreased energy and loss of interest, patients with depressive symptoms may profit less from this intervention than patients with less depressive symptoms. Furthermore, a recent study in patients with cardiovascular conditions reported a significant association between low self‐esteem and non‐compliance . The results of the present study have shown that QoL, self‐esteem, and depressive symptoms are highly interactive in patients with olfactory dysfunction.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that specific olfactory perfor- Furthermore, a recent study in patients with cardiovascular conditions reported a significant association between low self-esteem and non-compliance. 28 The results of the present study have shown that QoL, self-esteem, and depressive symptoms are highly interactive in patients with olfactory dysfunction. Therefore, these variables should be taken into account in patients with smell disorder, in order to provide a personalised intervention approach adapted to the individual needs of the patient.…”
Section: Comparison With Other Studiesmentioning
confidence: 49%